The postcolonial exotic : marketing the margins - Huggan, Graham, 1958- (London : Routledge, Taylor & Francis Group, 2001)
Travel writing, it has been said, helped produce the rest of the world for a Western audience. Could the same be said more recently of postcolonial writing? In The Postcolonial Exotic, Graham Huggan examines some of the processes by which value is attributed to postcolonial works within their cultural field. Using varied methods of analysis, Huggan discusses both the exoticist discourses that run through postcolonial studies and the means by which postcolonial products are marketed and domesticated for Western consumption.
Introduction: writing at the margins: postcolonialism, exoticism and the politics of cultural value -- 1. African literature and the anthropological exotic -- 2. Consuming India -- 3. Staged marginalities: Rushdie, Naipaul, Kureishi -- 4. Prizing otherness: a short history of the Booker -- 5. Exoticism, ethnicity and the multicultural fallacy -- 6. Ethnic autobiography and the cult of authenticity -- 7. Transformations of the tourist gaze: Asia in recent Canadian and Australian fiction -- 8. Margaret Atwood, Inc., or, some thoughts on literary celebrity -- Conclusion: thinking at the margins: postcolonial studies at the millennium
Obsahuje bibliografické odkazy a rejstřík
Elektronická reprodukce.
Keywords: 20. století; anglicky psaná literatura -- 20. století; postkoloniální literatury -- anglicky mluvící země -- 20. století; menšinová literatura -- anglicky mluvící země -- 20. století; literární náměty; postkolonialismus; exotika; multikulturalismus; etnicita; literárněvědné rozbory; literature in English -- 20th century; postcolonial literature -- English speaking countries -- 20th century; minority literature -- English speaking countries -- 20th century; literary themes; postcolonialism; exoticism; multiculturalism; ethnicity; literary criticism and history; monografie; e-knihy online; monographs; e-books online